Book review: A Dictionary of Geology and Earth Sciences (5th Edition), by Michael Allaby, 2020. Oxford University Press Academic UK, 720 pages, eBook price £14.99, ISBN: 9780198839033 - Berkowski, Błażej (Geologos, 2023)
Book review: A Dictionary of Geology and Earth Sciences (5th Edition), , by Michael Allaby, 2020. Oxford University Press Academic UK, 720 pages, eBook price £14.99, ISBN: 9780198839033.